PENGARUH PENERAPAN ANGGARAN BERBASIS KINERJA, KOMPETENSI APARATUR PEMERINTAH DAN KETAATAN ATAS PERATURAN PERUNDANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (AKIP) (Studi Kasus Pada OPD Di Kabupaten Rokan Hulu) - Muntakoh Ahmad; Surya Adri Satriawan Raja; Supriono Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to seek empirical evidence of the Effect of Performance-Based Budget Implementation, Government Apparatus Competence and Compliance with Regulations on Accountability of Government Institutions Performance (study case on OPD in Rokan Hulu Regency). This study used a questionnaire method. The questionnaire method is a questionnaire that is filled in and answered by the respondents who carry out local government functions. The research sample was 87 people. Hypothesis testing is carried out using Multiple Linear Regression Analysis. The statistical test tool used is the Statistical Product and Service Solution (SPSS) ver. 21.0 for Windows and Microsoft Excel 2010. The results showed that the implementation of performance-based budgeting has a significant effect on the accountability of government performance, the competence of government officials has a significant effect on the accountability of government performance, and compliance with laws and regulations has a significant effect on the accountability of government performance.Keywords: Implementation of Performance-Based Budgeting, Competence of Government Officials and Compliance with Laws and Regulations on Performance Accountability of Government Agencies (AKIP)